2021
DOI: 10.3390/molecules26164979
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Higher Alcohols in Wine: Implication on Aroma and Palate Attributes during Chardonnay Aging

Abstract: The higher alcohols 2-phenylethanol, tryptophol, and tyrosol are a group of yeast-derived compounds that have been shown to affect the aroma and flavour of fermented beverages. Five variants of the industrial wine strain AWRI796, previously isolated due to their elevated production of the ‘rose-like aroma’ compound 2-phenylethanol, were characterised during pilot-scale fermentation of a Chardonnay juice. We show that these variants not only increase the concentration of 2-phenylethanol but also modulate the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Previously it has been reported that T. delbrueckii produces less acetaldehyde than S cerevisiae [54]. Our headspace results with Prelude alone accorded with that finding, but notably when the fermentation was completed sequentially by CZ, the headspace acetaldehyde concentration rose almost 25-fold.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously it has been reported that T. delbrueckii produces less acetaldehyde than S cerevisiae [54]. Our headspace results with Prelude alone accorded with that finding, but notably when the fermentation was completed sequentially by CZ, the headspace acetaldehyde concentration rose almost 25-fold.…”
Section: Discussionsupporting
confidence: 91%
“…Given the considerable differences, further work to identify their source is warranted. Higher alcohols are substrates for acetate ester production [54].…”
Section: Discussionmentioning
confidence: 99%
“…For the Grenache wines, the above compounds together with those of fermentationderived compounds (esters, acids, and alcohols) and monoterpene and norisoprenoid compounds were quantified at the time of sensory evaluation using previously described methods [38].…”
Section: Analysis Of Aroma Compoundsmentioning
confidence: 99%
“…In addition, the consumption of glycine, tyrosine, leucine and lysine was positively correlated with the formation of fusel alcohols and acetate esters (Scott et al ., 2021). β‐Phenylethyl alcohol is derived from phenylalanine and associated with a rose‐like odour quality (Cordente et al ., 2021). Therefore, rice protein probably influences the flavour of Chinese rice wine, and an essential study needs to be launched on the characteristics of different rice protein fermentations.…”
Section: Introductionmentioning
confidence: 99%